2018
DOI: 10.1371/journal.pntd.0006864
|View full text |Cite
|
Sign up to set email alerts
|

Defining stopping criteria for ending randomized clinical trials that investigate the interruption of transmission of soil-transmitted helminths employing mass drug administration

Abstract: The current World Health Organization strategy to address soil-transmitted helminth (STH) infections in children is based on morbidity control through routine deworming of school and pre-school aged children. However, given that transmission continues to occur as a result of persistent reservoirs of infection in untreated individuals (including adults) and in the environment, in many settings such a strategy will need to be continued for very extended periods of time, or until social, economic and environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Knowledge regarding the extent of compliance within a population targeted for treatment can contribute towards an understanding of whether or not to stop randomised STH control trials, such as DeWorm3, earlier than originally planned [18,21]. If compliance is consistently poor there is little point in continuing treatment, monitoring and evaluation since transmission elimination is unlikely to occur.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Knowledge regarding the extent of compliance within a population targeted for treatment can contribute towards an understanding of whether or not to stop randomised STH control trials, such as DeWorm3, earlier than originally planned [18,21]. If compliance is consistently poor there is little point in continuing treatment, monitoring and evaluation since transmission elimination is unlikely to occur.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of successive rounds of MDA on STH prevalence is the primary focus of the Bill & Melinda Gates Foundation funded DeWorm3 project in India, Malawi and Benin [18]. This project is investigating whether a communitywide MDA-only approach to STH treatment, would be sufficient to reach a prevalence threshold below which helminth parasite populations cannot sustain transmission, thus leading to transmission elimination [19][20][21]. All STH species reproduce sexually within a human host to produce fertile eggs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite reductions in morbidity, in areas of endemic infection the current approach focusing on morbidity control may not reduce the overall prevalence of infection below levels needed to interrupt transmission[ 5 , 6 ]. Poor sanitation and hygiene, coupled with large reservoirs of infection in untreated individuals (including non-pregnant adults and children missed by current programs), serve to perpetuate transmission in many low-resource settings.…”
Section: Introductionmentioning
confidence: 99%
“…A recent trial in Kenya demonstrated that community-wide treatment was more effective than school-based treatment in reducing hookworm prevalence and intensity[ 9 ]. Mathematical models suggest that transmission interruption of STH may be possible with MDA alone, provided coverage of a substantial portion of the community is achieved repeatedly and individual compliance to treatment is high over many rounds of treatment[ 6 ]. The feasibility of such an approach depends on the underlying transmission intensity in a community, which is affected by a variety of factors including the demography of the targeted population, levels of access to clean water and sanitation, hygiene behaviours, population movement, and characteristics of the built and natural environment, as well as the intensity and frequency of prior deworming in the population[ 5 ].…”
Section: Introductionmentioning
confidence: 99%